Shape memory effect of NOA-63 polymer and its application in cell culture - Chua, Yuan Hong. (2013)
Cell culture substrates of defined topography have emerged as powerful tools to investigate cell growth and proliferation. However, current technologies only allow passive control of substrate properties. Hence a thermo-responsive cell culture system that uses shape memory polymer (SMP) substrates was introduced as the substrates can be programmed to change surface topography during cell culture. It was presumed that a shape memory-activated change in substrate topography could be used to control cell behaviour. To test this hypothesis, several tests and experiments were carried out to prove that shape memory properties exist in the chosen polymer. A flat SMP substrate was then embossed with patterns to produce a temporary topography of parallel micron-scale grooves. After plating cells on the substrate, shape recovery was triggered using a change in temperature tailored to be compatible with plant cell culture, thereby causing topographic recovery of the substrate back to its original flat surface. Alignment of the cell body and microfilaments along the grooves of the temporary topography was significantly improved using the substrate. These results demonstrate control of cell behaviour using shape-memory-activated topographic changes. This facilitates the investigation of cell biomechanical function, and cell soft-matter physics with the use of active cell culture.